Adult Civic Educators’ Educational Needs Assessment in the Context of South Korea - Joon Heo; Jihyun Kim; Yeji Lee (Adult Education Research Conference, 2022)
This study measured current and required levels of educational capacities of adult civic educators in South Korea. The pairwise comparisons provided implications for more urgent and important professional development areas.
Keywords: adult civic education; educators’ needs assessment; democracy education